Municipal Bond Markets - Cestau, Dario; Hollifield, Burton; Li, Dan; Schürhoff, Norman (Anual Reviews, 2019)
The effective functioning of the municipal bond market is crucial for the provision of public services, as it is the largest capital market for state and municipal issuers. Prior research has documented tax, credit, liquidity, and segmentation effects in municipal bonds. Recent regulatory initiatives to improve transparency have made granular trade data available to researchers, rendering the municipal bond market a natural laboratory for the study of financial intermediation, asset pricing in decentralized markets, and local public finance. Trade-by-trade studies have found large trading costs, contemporaneous price dispersion, and other deviations from the law of one price. More research is required to understand optimal market design and the impact of post-crisis regulation, sustainability, and financial technology
Keywords: Municipal bonds; Muni-bond puzzle; Over-the-counter markets; Trading cost; Centrality premium; Electronification; Green bonds; 53 Ciencias Económicas::5307 Teoría económica; ODS 8 - Trabajo decente y crecimiento económico; ODS 17 - Alianzas para lograr los objetivos